Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT Nagamas Kurnia Sejahtera - Markus Aryanto Sitorus; Dedi Supiyadi (Universitas Persada Indonesia YAI, 2026)
The purpose of this study is to describe PT Nagamas Kurnia Sejahtera's pay, workplace, and employee performance, a textile manufacturer in Bandung Regency, and to test how far these two variables shape employee performance, both individually and jointly. A quantitative design combining descriptive and verificative approaches was applied, drawing on 100 workers selected using purposive sampling. A Likert-scale questionnaire was used to collect the data, which were then processed using multiple linear regression in SPSS. The results show that employee performance, work environment, and compensation are all in the good category, scoring 81.6%, 83.0%, and 82.6% respectively. Compensation (t = 4.809; sig = 0.000) and work environment (t = 4.179; sig = 0.000) both have a favorable and significant impact on employee performance, according to the t-test. Meanwhile, the F-test shows that employee performance is positively and significantly impacted by both compensation and work environment (F = 53.190; sig = 0.000), accounting for 52.3% of the variance. Overall, the study concludes that strengthening the compensation system alongside improving the work environment can meaningfully raise employee performance within textile manufacturing companies.